Pengaruh Penerapan Model Problem Based Learning (PBL) Menggunakan Pendekatan Teaching at The Right Level (TaRL) Terhadap Minat Dan Kemampuan Menulis Deskripsi Siswa Kelas 5 Gugus 3 Kecamatan Makassar - Aryasti, Andi; Akhir, Muhammad; Tarman, Tarman (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to describe students' interest and writing ability using the Problem-Based Learning model combined with the Teaching at the Right Level (TaRL) approach. This research is a quantitative study. The sample consisted of all fifth-grade students at UPT SPF SD Inpres Maccini 1/1. Data were collected through tests and observations, and the results were analyzed using descriptive and inferential statistics through a t-test. Based on the average posttest results of interest and descriptive writing skills using the Problem-Based Learning model with the Teaching at the Right Level approach, the posttest scores were higher than the pretest scores. The research findings show that the average interest score of the control and experimental classes was 86.44 ≤ 93.27, and the average descriptive writing ability score of the control and experimental classes was 83.00 ≤ 95.18. After administering a written test to students, the average pretest score before implementing the model was 63.91%. Following the intervention, the average posttest score increased to 87.73%. Thus, the implementation of the Problem-Based Learning model with the Teaching at the Right Level approach in Indonesian language learning had a positive effect on students' interest and descriptive writing skills